HUBUNGAN ANTARA KADAR HEMOGLOBIN DENGAN TINGKAT KEPARAHAN PENYAKIT PASIEN SYSTEMIC LUPUS ERITHEMATOSUS DI RSUP SANGLAH - Putu Cyntia Ratnadi; Ketut Suega; Ni Made Renny Anggraeni Rena (Universitas Udayana, 2016)
THE ASSOCIATION BETWEEN HEMOGLOBIN LEVEL WITH DISEASE SEVERITY IN PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS IN SANGLAH GENERAL HOSPITALSystemic lupus erythematosus (SLE) is a chronic multisystem autoimmune disease with a wide spectrum of manifestations. Anemia is one of the hematologic manifestations of SLE that occurred frequently due to suppression of erythropoiesis by the presence of chronic inflammation. Severity of anemia often reflected an underlying condition, including SLE. The lower levels of hemoglobin (Hb), usually related to more severe underlying disease. This study was conducted to determine the association between Hb level with disease severity in patients with SLE. This study was an observational analytic study with cross-sectional study. The sample were SLE patients who treated in Sanglah General Hospital. We observed medical records SLE patients in the period of January-December 2014. The independent variable was severity of SLE and dependent variable was hemoglobin level. Statistic analysis used chi square. Forty one patients aged 17-74 y.o, mean 33.46±11.61 y.o were included in this study. Majority of SLE patients were woman (n=38). Hb level was ranging from 3.00-16.10 g/dl, mean 10.09±2.92 g/dl. Low Hb level was occurred in 29 subjects (70.70%), 9 (31.00%) in mild disease and 20 (69.00%) in severe disease. The association between Hb level with severity of SLE was statistically significant (p<0.05).